The Age of Discontent: Italian Households at the Beginning of the Decade - Tito Boeri; Andrea Brandolini (Institute for the Study of Labor (IZA), 2005)
In the Italian public debate growing attention has been recently paid to ?household impoverishment?. Subjective indicators of economic condition show that this concern reflects a common sentiment of the Italian population. On the other hand, estimates based on the Bank of Italy?s Survey of Household Income and Wealth reveal a surprising stability of income distribution in the period 1993-2002, after the sharp widening amid the 1991-92 recession. A number of possible reasons that can account for this apparent inconsistency are investigated: data deficiencies; disappointed expectations; significant distributive changes across socio-economic groups which have cancelled out at the aggregate level; higher income mobility not captured by static inequality indices.
Keywords: D31; I3; 330; household confidence; income inequality; poverty; income mobility; Lebensstandard; Privater Haushalt; Haushaltseinkommen; Einkommensverteilung; Armut; Italien